Peran Kepemimpinan dalam Manajemen Media Massa: Studi Kasus Pada Lembaga Penyiaran Swasta - Nayla Anindia; Hasanatul Mardliyah Br Tambunan; Afwan Syahril Manurung (Bridge : Jurnal Publikasi Sistem Informasi dan Telekomunikasi, 2025)
This article aims to examine the role of leadership in mass media management through a case study of a private broadcasting institution in Indonesia. The focus of the research is on how leadership styles influence organizational performance, editorial decision-making, and operational effectiveness. A qualitative approach was employed, using in-depth interviews, participatory observation, and document analysis on a national private broadcasting institution. The findings reveal that visionary, communicative, and adaptive leadership plays a crucial role in fostering synergy across departments and enhancing responsiveness to the dynamics of the media industry. These results highlight the significance of strategic leadership in maintaining the sustainability and credibility of private broadcasting institutions amid the challenges of digitalization and increasingly competitive markets.